FRI0235 Cncomitant use of intravenous methylprednisolone to obtain higher retention rate of abatacept in rheumatoid arthritis. (15th June 2017) - Sawada, H; Suda, M; Kishimoto, M; Okada, M
Abstract : Background: Abatacept (ABT) is a widely used biologic for treating rheumatoid arthritis (RA). Objectives: Concomitant use of intravenous corticosteroids with ABT infusion may contribute to achieve earlier remission and higher retention rates. Methods: We conducted a retrospective cohort study at St. Luke's International Hospital, Tokyo, Japan, from January 2010 to June 2016. Patients who met the 2010 ACR/EULAR classification criteria for RA and treated with ABT were included in the study. We excluded patients who use two or more biologics prior to initiation of ABT. Our primary outcome was treatment retention rates of ABT at week 24. Secondary outcomes were changes in C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) during follow-up (week 0 vs. week 8). We compared these outcomes between the patients receiving concomitant intravenous methylprednisolone (mPSL) with first 3 consecutive doses of ABT and those not receiving it. Log-rank analysis and Fisher's exact test were applied for statistical analysis. Results: 64 RA patients were included in the study. Mean age was 67.3 (± 14.2) and 55 (85.9%) were female. Among them, 13 (20.3%) received concomitant ABT with mPSL. The dosage of mPSL ranged from 30mg to 250mg (median dosage was 40mg). At week 24, the cumulative retention rates of the patients receiving mPSL (mPSL group) and those not receiving it (non-mPSL group) were 92.3% and 76.5%, respectively. There was no significant difference in the retention rates between the two groups (log-rank test, p=0.21) (figure). Changes in CRP between week 0 vs. week 8 were -1.56 mg/dl (± 2.92) in mPSL group and -1.08 mg/dl (± 2.17) in non-mPSL group (p=0.22), and those in ESR were -8.23 mm/h (± 18.40) in mPSL group and -6.61 mm/h (± 17.93) in non-mPSL group (p=0.75), respectively. Conclusions: This is the first real world study to investigate whether ABT administrated with intravenous mPSL maintain higher retention rates in rheumatoid arthritis. Though there was no statistically significant difference, the retention rates of ABT at 24 weeks were higher among patients receiving ABT and mPSL concomitantly, compared with ABT mono-therapy group. It may reflect rapid improvement of the disease activity. Disclosure of Interest: None declared